Form versus function: theory and models for neuronal substrates$nElektronische Ressource - Petrovici, Mihai A. (Springer, 2016)
Prologue -- Introduction: From Biological Experiments to Mathematical Models -- Artiﬁcial Brains: Simulation and Emulation of Neural Networks -- Dynamics and Statistics of Poisson-Driven LIF Neurons -- Cortical Models on Neuromorphic Hardware -- Probabilistic Inference in Neural Networks -- Epilogue.
Keywords: Hochschulschrift